Target Trial Emulation: Impact of C-Section on Birth Outcomes for Spontaneous Preterm Breech Presentations - Robin Alexander; Holger Unger; Swetha Bhaskar; Ben Swallow; Stefan Unger; Amaya Azcoaga-Lorenzo; Adeniyi Fagbamigbe; Sarah Stock; Colin McCowan (International Journal of Population Data Science, 2024)
Breech presentation is a risk factor for poor birth outcomes. Guidance for safest mode of delivery in breech presenting full term pregnancies is available but there is a lack of evidence on the optimal mode of delivery in breech presenting preterm spontaneous births. The aim of this study is to evaluate the causal effect of mode of delivery on extended perinatal death (EPD) in this population using a trial emulation.